Thermal divide andesites - trachytes, petrologic evidence, and implications from Jurassic north Patagonian massif alkaline volcanism - Aragon, Eugenio (2003)
The Andesitas Alvar Formation is part of the large Jurassic volcanic province of Patagonia (southern South America) that, in Jurassic time, participated in the disassembling of Gondwana in a tensional-transtensional regime with large-scale half-grabens. This large igneous province contains alkaline and calc-alkaline series of andesite-trachyte, trachyte-rhyolite, and andesite-dacite trends. Four-phase experimental diagrams of Qz-Or-Ab-An and Ab-An-Ol-Di correlate with the TAS diagram and explain the Andesitas Alvar Formation's sodium-rich andesite-trachyte, which evolved through a thermal divide edge. This alkaline set initially included the paragenesis olivine-plagioclase-diopsidic augite, which was later replaced by hornblende-plagioclase-diopsidic augite. The andesite-trachyte trend is saturated in silica and rich in sodium and alumina. Diopsidic augite, plagioclase, and hornblende crystals are reverse zoned in magnesium, iron, calcium, and sodium, so the sodium-rich cores of plagioclase are not due to contamination, and the magmas mix several batches of partial melts of basic rock. Crystallization temperatures and pressures show that magma chamber emplacement and thermal reversal took place mainly at 4 kb. This is interpreted as the emplacement of collecting chambers at the brittle-ductile transition in the crust, where mixing and crystallization took place, followed by rapid extrusion in a transtensional tectonic environment. © 2003 Elsevier Ltd. All rights reserved.